2018
DOI: 10.1016/j.ymben.2018.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota dysbiosis is associated with malnutrition and reduced plasma amino acid levels: Lessons from genome-scale metabolic modeling

Abstract: Malnutrition is a severe non-communicable disease, which is prevalent in children from low-income countries. Recently, a number of metagenomics studies have illustrated associations between the altered gut microbiota and child malnutrition. However, these studies did not examine metabolic functions and interactions between individual species in the gut microbiota during health and malnutrition. Here, we applied genome-scale metabolic modeling to model the gut microbial species, which were selected from healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 101 publications
(126 reference statements)
1
89
0
3
Order By: Relevance
“…FBA operates under the steady-state assumption and as such does not require kinetic parameters to compute an optimal solution [9]. Through implementation of condition-specific constraints, e.g., a certain dietary regime, COBRA simulations have provided further insight into the metabolic capabilities of, e.g., human intestinal microbes [10][11][12][13][14], for which a comprehensive collection of reconstructions (AGORA) has been published [15,16]. An advantage of the COBRA approach for microbial community modeling is that the underlying genome-scale metabolic networks enable mechanistic predictions of metabolic fluxes in each individual species while taking into account biological features, such as substrate availability or species-species boundaries [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FBA operates under the steady-state assumption and as such does not require kinetic parameters to compute an optimal solution [9]. Through implementation of condition-specific constraints, e.g., a certain dietary regime, COBRA simulations have provided further insight into the metabolic capabilities of, e.g., human intestinal microbes [10][11][12][13][14], for which a comprehensive collection of reconstructions (AGORA) has been published [15,16]. An advantage of the COBRA approach for microbial community modeling is that the underlying genome-scale metabolic networks enable mechanistic predictions of metabolic fluxes in each individual species while taking into account biological features, such as substrate availability or species-species boundaries [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…An advantage of the COBRA approach for microbial community modeling is that the underlying genome-scale metabolic networks enable mechanistic predictions of metabolic fluxes in each individual species while taking into account biological features, such as substrate availability or species-species boundaries [17,18]. Previous studies have already demonstrated the use of constraint-based multi-species models for the prediction of host-microbe interactions [12,19] and gut microbial community interactions [13,20]. COBRA models can also be contextualized through omics data, e.g., metagenomic data [2,14].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the metabolites predicted to be exchanged have been observed in the gut and implicated in the maintenance of host-microbiota homeostasis as well as human health and disease. For example, a possible alanine exchange predicted by the same microbial model collection used here was confirmed in vitro 43 , increased isoleucine levels have been associated with improved growth in humans 44 , and consumption of glycine by the microbiota has been shown to reduce glycine levels in the host, which has been associated with non-alcoholic fatty liver disease (NAFLD), obesity, and type 2 diabetes 45 .…”
Section: Metabolite Exchanges In the Human Gutmentioning
confidence: 57%
“…Beyond popular applications, such as metabolic flux prediction with flux balance analysis and prediction of the gene essentiality, GSMNs have been used in numerous applications (38) , e.g. chemicals and materials production (39)(40)(41)(42) , drug targeting (43,44) , human metabolism, disease understanding (45,46) and, multi-organism interaction modeling (47,48) . MNXref is now used within tools for testing GSMNs such as MEMOTE (49) , and has been proposed as a reference for minimal standard content for metabolic network reconstruction (50) .…”
Section: Discussionmentioning
confidence: 99%